Implementasi Forward Chaining Dalam Sistem Pakar Diagnosa Kecanduan Pada Game Online - Nuraeni, Fitiri; Baswardono, Wiyoga; Rahadian, Reza (Institut Teknologi Garut, 2025)
The rapid advancement of technology has led to the emergence of various types of technology that can be found around us. One of the technological advancements that can be experienced is the presence of entertainment media in the form of online games. Online games are a type of game connected through the internet and can be played on devices such as computers (PCs), laptops, smartphones, and other platforms.Online games have had a significant impact on Indonesian society, especially among teenagers. The number of online game players in Indonesia has reached 64.5%, making it one of the countries with the highest number of players worldwide. Games such as Mobile Legends, Arena of Valor, Clash of Clans, and Player Unknown’s Battleground dominate recreational activities across different social groups, regardless of culture, age, or gender.Besides providing an engaging gaming experience, online games also offer positive impacts, such as training discipline, communication, and teamwork through their collaborative features. However, increasing interest in online games can lead to addiction problems, particularly among teenagers. This phenomenon may result in changes in social behavior and psychological well-being.This study proposes a solution by designing and developing an Expert System application for diagnosing online game addiction. The method used in this research is forward chaining. The methodology applied in this study follows ESDLC, as it serves as a fundamental concept for the design and development of expert systems.